Virtual Discontent: Japanese Netizen Reactions to the Indonesia-China High-Speed Rail Controversy on Youtube - Amanullah, Moh Gandhi; Elsy, Putri (Universitas Gadjah Mada, 2024)
This study delved into the reactions of Japanese society, particularly netizens, to the Indonesia-China High-Speed Rail project, inaugurated in 2023, by analyzing content on Youtube. Through a qualitative approach and content analysis, the research applied symbolic interactionism as its conceptual framework. The dataset included 22 Youtube videos collected during October 2023, a pivotal time marked by the project's inauguration. This study revealed that, through a symbolic interactionism perspective, Japanese netizens form negative meanings of the Indonesia-China High Speed Rail (HSR) project based on interactions with symbols in Youtube content. Visual and verbal representations in videos and thumbnails contributed to these perceptions, with 20 out of 22 analyzed contents expressing criticism, sarcasm, or disappointment, portraying HSR as a symbol of failure or betrayal, rather than progress or achievement. In addition, discussions in the comments section, with an average of 390 comments per video, reinforced these negative interpretations. Phrases such as “betrayal” and visuals that negatively portray Indonesia emphasize a broader sense of national disillusionment, going beyond the technical aspects of the project and reflecting political as well as economic concerns.